Positive electrode active material, positive electrode comprising same, and secondary battery

CN116615820BActive Publication Date: 2026-10-16LG ENERGY SOLUTION LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202280008335.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-24
Filing Date
2022-02-24
Publication Date
2026-10-16
Estimated Expiration
2042-02-24

AI Technical Summary

Technical Problem

另外,因为电解质溶液穿过微裂纹渗入正极活性材料而使活性材料结构劣化,并通过包含于正极活性材料中的过渡金属加速电解质溶液分解,所以寿命特性迅速劣化,并因此可能由于电解质溶液分解导致的膜形成使内阻增加而发生输出特性下降的问题

Benefits of technology

[0014] Because the positive electrode active material of the present invention has a structure in which the average grain size of the core is smaller than that of the shell, the occurrence of core defects (such as microcracks) and film formation due to electrolyte solution decomposition can be suppressed. Furthermore, by maintaining a larger average grain size than the core, the shell has advantages in capacity characteristics and its reactivity with the electrolyte solution can be reduced due to its smaller specific surface area. Therefore, the positive electrode active material of the present invention has capacity characteristics comparable to conventional positive electrode active materials, while also exhibiting better lifetime characteristics.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material and a method for manufacturing the same, which is developed to be able to suppress decomposition of an electrolyte solution and occurrence of microcracks of a positive electrode active material during charge and discharge by forming an average grain size of a core part of a high-nickel positive electrode active material to be smaller than an average grain size of a shell part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Cross-reference to related applications

[0002] This application claims priority to Korean Patent Application No. 10-2021-0024668, filed on February 24, 2021, the disclosure of which is incorporated herein by reference. Technical Field

[0004] This invention relates to positive electrode active materials having a core-shell structure, and more particularly, to a positive electrode active material and a method for preparing the same, wherein lifetime characteristics are improved while capacity characteristics are maintained by making the average grain size of the core portion of the positive electrode active material particles smaller than the average grain size of the shell portion. Background Technology

[0005] With technological advancements, the demand for rechargeable batteries as an energy source has increased significantly, as has the demand for mobile devices. Among rechargeable batteries, lithium-ion batteries, characterized by high energy density, high voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used.

[0006] With the recent technological advancements in electric vehicles, the demand for high-capacity rechargeable batteries is increasing. However, while increasing the grain size of primary batteries to enhance capacity, the lattice structure deforms during lithium-ion insertion and extraction during charging and discharging, making them prone to microcracks. Furthermore, the electrolyte solution penetrates these microcracks into the positive electrode active material, degrading its structure. This, coupled with the accelerated electrolyte decomposition by transition metals contained within the positive electrode active material, leads to a rapid decline in lifetime characteristics. Consequently, the formation of a film due to electrolyte decomposition can increase internal resistance, potentially causing a decrease in output characteristics.

[0007] Therefore, it is necessary to develop positive electrode active materials with excellent lifetime characteristics and high capacity. Summary of the Invention

[0008] Technical issues

[0009] One aspect of the present invention provides a positive electrode active material and a method for preparing the same, which is developed by forming the core of a high-nickel positive electrode active material with an average grain size smaller than that of the shell, thereby suppressing the decomposition of the electrolyte solution and the occurrence of microcracks in the positive electrode active material during charge and discharge.

[0010] Technical solution

[0011] According to one aspect of the present invention, a positive electrode active material for a secondary battery is provided, comprising lithium transition metal oxide particles having a core-shell structure comprising a core and a shell disposed on the surface of the core, wherein the average grain size of the core is smaller than the average grain size of the shell, and the nickel content in all transition metals contained in the core and the shell is 80 atm% or more.

[0012] According to another aspect of the present invention, a positive electrode is provided, comprising the positive electrode active material described in the present invention; and a secondary battery comprising said positive electrode.

[0013] Beneficial effects

[0014] Because the positive electrode active material of the present invention has a structure in which the average grain size of the core is smaller than that of the shell, the occurrence of core defects (such as microcracks) and film formation due to electrolyte solution decomposition can be suppressed. Furthermore, by maintaining a larger average grain size than the core, the shell has advantages in capacity characteristics and its reactivity with the electrolyte solution can be reduced due to its smaller specific surface area. Therefore, the positive electrode active material of the present invention has capacity characteristics comparable to conventional positive electrode active materials, while also exhibiting better lifetime characteristics. Detailed Implementation

[0015] The invention will be described in more detail below.

[0016] It is understood that the words or terms used in the specification and claims should not be interpreted as having the meaning defined in a common dictionary, and it will be further understood that, based on the principle that the inventor may appropriately define the meaning of words or terms to best interpret the invention, these words or terms should be interpreted as having the meaning consistent with their meaning in the relevant technical field and in the technical concept of the invention.

[0017] In this invention, the term "core" refers to the region containing the center of the positive electrode active material, wherein it represents a region with a small average grain size of 100 nm to 180 nm.

[0018] In this invention, the term "shell" refers to the region containing the surface of the positive electrode active material, wherein it represents a region with an average grain size greater than that of the core, ranging from 180 nm to 250 nm.

[0019] In this invention, the term "grain" refers to a single crystal unit having a regular arrangement of atoms. The size of the grain can be measured, for example, using a TITAN G2 high-resolution transmission electron microscope (HR-TEM) to magnify the sample surface 800,000 to 2 million times, and the average grain size can be measured by obtaining the arithmetic mean of the measured individual grain sizes.

[0020] In this invention, the term "primary particle" refers to the smallest particle unit that can be classified into a single bulk when the cross-section of the positive electrode active material precursor is observed by scanning electron microscopy (SEM). This particle may consist of a single grain or multiple grains.

[0021] In this invention, the term "secondary particle" refers to a secondary structure formed by the aggregation of multiple primary particles. The average particle size of the secondary particles can be measured using a particle size analyzer, and in this invention, a Microtrac S3500 is used as the particle size analyzer.

[0022] In this invention, the term "particle size Dn" for a positive electrode active material represents the particle size at n% of the cumulative particle size distribution. Specifically, D50 is the particle size at 50% of the cumulative particle size distribution, D90 is the particle size at 90% of the cumulative particle size distribution, and D10 is the particle size at 10% of the cumulative particle size distribution. Dn can be measured using laser diffraction. Specifically, after dispersing the target powder in a dispersion medium, the dispersion medium is introduced into a commercially available laser diffraction particle size measurement device (e.g., Microtrac S3500), and the particle size distribution is calculated by measuring the difference in diffraction patterns caused by particle size as the particles pass through the laser beam. D10, D50, and D90 can be measured by calculating the particle size at 10%, 50%, and 90% of the cumulative particle size distribution using this measurement device.

[0023] Positive electrode active material

[0024] The positive electrode active material of the present invention may comprise lithium transition metal oxide particles having a core-shell structure, comprising a core and a shell disposed on the surface of the core.

[0025] Of all the transition metals contained in the core and shell of the positive electrode active material of the present invention, the nickel content can be 80 atm% or more. If the nickel content is less than 80 atm%, the capacity of the positive electrode active material decreases, which may prevent the positive electrode active material from being used in electrochemical devices requiring high capacity.

[0026] Specifically, the average grain size of the core can be in the range of 100 nm to 180 nm, preferably 110 nm to 170 nm, and more preferably 120 nm to 160 nm. When the average grain size of the core of the positive electrode active material for lithium secondary batteries meets the above range, excellent lifetime characteristics can be obtained while maintaining the high capacity of the lithium secondary battery.

[0027] The core may have a composition represented by the following chemical formula 1.

[0028] [Chemical Formula 1]

[0029] Li x1 Ni a1 Co b1 Mn c1 Al d1 M 1 e1 O2

[0030] In Chemical Formula 1, M 1 may be at least one selected from the group consisting of zirconium (Zr), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P) and sulfur (S), and in terms of improving the structural stability of the lithium transition metal oxide, M 1 particularly preferably includes Zr.

[0031] x1 represents the molar ratio of lithium in the lithium transition metal oxide, wherein x1 may satisfy 0.90≤x1≤1.2, preferably 0.95≤x1≤1.08, and more preferably 1≤x1≤1.08.

[0032] a1 represents the molar ratio of nickel in the metal elements other than lithium in the lithium transition metal oxide, wherein a1 may satisfy 0.80≤a1≤0.95 or 0.83≤a1≤0.93. When the nickel content satisfies the above range, high capacity characteristics can be achieved.

[0033] b1 represents the molar ratio of cobalt in the metal elements other than lithium in the lithium transition metal oxide, wherein b1 may satisfy 0<b1<0.20, 0<b1≤0.15 or 0.01≤b1≤0.10. The content of cobalt may vary depending on the contents of nickel, manganese, aluminum and M 1 . In the case where the cobalt content is excessively high, there are problems that the overall raw material cost increases and the reversible capacity decreases, and in the case where the cobalt content is excessively low, there is a problem that it is difficult to simultaneously achieve sufficient rate performance and high powder density of the battery.

[0034] c1 represents the molar ratio of manganese in the metal elements other than lithium in the lithium transition metal oxide, wherein c1 may satisfy 0<c1<0.20, 0<c1≤0.15 or 0.01≤c1≤0.10. In the case where the manganese content is excessively high, a problem may occur in achieving high capacity, and in the case where the manganese content is excessively low, there is a problem that the production cost increases.

[0035] d1 represents the molar ratio of aluminum in the metal elements other than lithium in the lithium transition metal oxide, wherein d1 may satisfy 0<d1<0.20, 0<d1≤0.15 or 0.01≤d1≤0.10. When the aluminum content is excessively high, there is a problem of increased internal resistance, and when the aluminum content is excessively low, there is a problem of increased production cost.

[0036] e1 represents M 1 the molar ratio in the metal elements other than lithium in the lithium transition metal oxide, wherein e1 may satisfy 0≤e1<0.10 or 0≤e1≤0.05.

[0037] The average grain size of the shell portion may be in the range of 180 nm to 250 nm, preferably 190 nm to 230 nm, and more preferably 200 nm to 220 nm. When the average grain size of the shell portion of the positive electrode active material for lithium secondary batteries satisfies the above range, the effect of optimizing the reaction surface area between the positive electrode active material and the electrolytic solution can be obtained, and the capacity of the lithium secondary battery can be increased at the same time.

[0038] The shell portion may have a composition represented by the following Chemical Formula 2.

[0039] [Chemical Formula 2]

[0040] Li x2 Ni a2 Co b2 Mn c2 Al d2 M 2 e2 O2

[0041] In Chemical Formula 2, M 2 may be at least one selected from Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P and S, and in terms of improving the structural stability of the lithium transition metal oxide, M 2 particularly preferably includes Zr.

[0042] x2 represents the molar ratio of lithium in the lithium transition metal oxide, wherein x2 may satisfy 0.90≤x2≤1.2, preferably 0.95≤x2≤1.08, and more preferably 1≤x2≤1.08.

[0043] a2 represents the molar ratio of nickel in the metal elements other than lithium in the lithium transition metal oxide, wherein a2 may satisfy 0.83≤a2<1.0 or 0.85≤a2≤0.99. When the nickel content satisfies the above range, high capacity characteristics can be achieved.

[0044] b2 represents the molar ratio of cobalt in the metal elements other than lithium in the lithium transition metal oxide, where b2 may satisfy 0<b2<0.20, 0<b2≤0.15, or 0.01≤b2≤0.10. The content of cobalt may vary depending on the contents of nickel, manganese, aluminum and M 2 . When the cobalt content is excessively high, there are problems that the overall raw material cost increases and the reversible capacity decreases, while when the cobalt content is excessively low, there is a problem that it is difficult to simultaneously achieve sufficient rate performance and high powder density of the battery.

[0045] c2 represents the molar ratio of manganese in the metal elements other than lithium in the lithium transition metal oxide, where c2 may satisfy 0<c2<0.20, 0<c2≤0.15, or 0.01≤c2≤0.10. When the manganese content is excessively high, a problem may arise in achieving high capacity, while when the manganese content is excessively low, there is a problem that the production cost increases.

[0046] d2 represents the molar ratio of aluminum in the metal elements other than lithium in the lithium transition metal oxide, where d2 may satisfy 0<d2<0.20, 0<d2≤0.15, or 0.01≤d2≤0.10. When the aluminum content is excessively high, there is a problem that the internal resistance increases, while when the aluminum content is excessively low, there is a problem that the production cost increases.

[0047] e2 represents M 2 the molar ratio in the metal elements other than lithium in the lithium transition metal oxide, where e2 may satisfy 0≤e2≤0.10 or 0≤e2≤0.05.

[0048] In one embodiment of the present invention, a1 described in Chemical Formula 1 of the core portion may be smaller than a2 described in Chemical Formula 2 of the shell portion.

[0049] In the positive electrode active material of the present invention, the average grain size of the core portion may be smaller than the average grain size of the shell portion. By making the average grain size of the core portion smaller than the average grain size of the shell portion in the high-nickel lithium transition metal oxide, the occurrence of defects (such as microcracks) in the core portion and film formation caused by decomposition of the electrolyte solution can be suppressed. In addition, the shell portion has the advantage of capacity characteristics by maintaining a larger average grain size than the core portion, and can reduce reactivity with the electrolyte solution due to a small specific surface area. Accordingly, when used in a battery, the positive electrode active material of the present invention can improve life characteristics while maintaining initial capacity characteristics and output characteristics.

[0050] Specifically, in the positive electrode active material for lithium secondary batteries of the present invention, the difference between the average grain size of the core and the average grain size of the shell can be in the range of 20 nm to 150 nm, preferably 30 nm to 100 nm, and more preferably 40 nm to 80 nm. When the difference between the average grain size of the core and the average grain size of the shell of the positive electrode active material for lithium secondary batteries meets the above range, when used in a battery, the positive electrode active material of the present invention can improve lifetime characteristics while maintaining initial capacity characteristics and output characteristics.

[0051] In addition, the positive electrode active material may further include a coating layer formed on its surface, wherein the coating layer may include at least one metal selected from B, aluminum (Al), Hf, niobium (Nb), Ta, molybdenum (Mo), silicon (Si), zinc (Zn) and Zr.

[0052] Because the coating layer inhibits side reactions by preventing contact between the positive electrode active material contained in the lithium secondary battery and the electrolyte solution, the coating layer can improve lifetime characteristics and also increase the packing density of the positive electrode active material.

[0053] The coating can be formed on the entire surface of the positive electrode active material or it can be formed locally. Specifically, when the coating is formed locally on the surface of the positive electrode active material, the coating can cover more than 20% of the total area of ​​the positive electrode active material. When the area of ​​the coating is less than 20%, the effect of the coating on improving lifetime characteristics and packing density may not be significant.

[0054] Furthermore, the coating layer can be formed at a thickness ratio of 1 / 10,000 to 1 / 100 relative to the average particle size of the positive electrode active material particles. If the thickness ratio of the coating layer to the positive electrode active material particles is less than 1 / 10,000, the effect of improving lifetime characteristics and packing density due to the formation of the coating layer may not be significant, and if the thickness ratio is greater than 1 / 100, there is a concern about a decrease in battery characteristics.

[0055] Methods for preparing positive electrode active materials

[0056] The method for preparing the positive electrode active material of the present invention may include the following steps: preparing a first solution containing a transition metal including nickel, cobalt, manganese and aluminum; simultaneously adding the first solution containing a transition metal, an alkaline aqueous solution and an ammonium cation complexing agent to a reactor, and forming core particles through a co-precipitation reaction; simultaneously adding a second solution containing a transition metal, an alkaline aqueous solution and an ammonium cation complexing agent to a reaction solution containing the core particles, and performing a co-precipitation reaction to form a shell on the core particles, thereby forming positive electrode active material precursor particles; and mixing the positive electrode active material precursor with a lithium-containing raw material and sintering the mixture.

[0057] The above description of the positive electrode active material can be applied to the method of preparing the positive electrode active material.

[0058] The steps of the method for preparing the positive electrode active material according to the present invention will be described in detail.

[0059] First, a first solution containing transition metals and a second solution containing transition metals, comprising nickel, cobalt, manganese and aluminum, are prepared.

[0060] The first solution containing a transition metal and the second solution containing a transition metal may, for example, contain nickel (Ni) raw materials, cobalt (Co) raw materials, manganese (Mn) raw materials and aluminum (Al) raw materials.

[0061] Nickel-containing raw materials may be, for example, nickel-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides or hydroxyoxides, and may specifically be Ni(OH)2, NiO, NiOOH, NiCO3·2Ni(OH)2·4H2O, NiC2O2·2H2O, Ni(NO3)2·6H2O, NiSO4, NiSO4·6H2O, nickel salts of fatty acids, nickel halides or combinations thereof, but the present invention is not limited thereto.

[0062] The cobalt (Co) raw material can be a cobalt-containing acetate, nitrate, sulfate, halide, sulfide, hydroxide, oxide or hydroxy oxide, and specifically can be Co(OH)2, CoOOH, Co(OCOCH3)2·4H2O, Co(NO3)2·6H2O, CoSO4, Co(SO4)2·7H2O or a combination thereof, but the present invention is not limited thereto.

[0063] Manganese (Mn) raw materials may be, for example, manganese-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides or hydroxyoxides or combinations thereof, and specifically may be manganese oxides (such as Mn2O3, MnO2 and Mn3O4), manganese salts (such as MnCO3, Mn(NO3)2, MnSO4, manganese acetate, manganese dicarboxylate, manganese citrate and manganese fatty acid salts), manganese hydroxyoxides, manganese chloride or combinations thereof, but the present invention is not limited thereto.

[0064] Aluminum (Al) raw materials may be, for example, aluminum-containing acetates, nitrates, sulfates, halides, sulfides, hydroxides, oxides or hydroxy oxides or combinations thereof, and specifically may be Al(OH)3, Al2O3, Al(OCOCH3)3, Al(NO3)3, Al2(SO4)3 or combinations thereof, but the present invention is not limited thereto.

[0065] A first solution containing a transition metal and a second solution containing a transition metal can be prepared by adding nickel-containing (Ni), cobalt-containing (Co), manganese-containing (Mn), and aluminum-containing (Al) raw materials to a solvent, specifically water, or a mixture of an organic solvent (e.g., ethanol) that can be uniformly mixed with water and water; or by mixing aqueous solutions of nickel-containing (Ni), cobalt-containing (Co), manganese-containing (Mn), and aluminum-containing (Al) raw materials.

[0066] According to the present invention, based on the total number of moles of transition metal, the first solution containing transition metal and the second solution containing transition metal may contain more than 80 atm% nickel.

[0067] As a method for controlling the grain size of the core and shell of a positive electrode active material, it may include, for example, a method of controlling the grain size of the core and shell by changing the transition metal composition. Specifically, it may be possible to change the nickel content of a first solution containing a transition metal and a second solution containing a transition metal, to change whether or not dopant elements are added to the core and shell respectively, or to change the amount of dopant elements added to the core and shell.

[0068] In one embodiment of the present invention, a solution containing transition metals can be prepared in a form in which a first solution containing transition metals contains nickel, cobalt, manganese and aluminum, and a second solution containing transition metals contains nickel, cobalt, manganese and aluminum, and has a higher molar fraction of nickel compared to the first solution containing transition metals.

[0069] In another embodiment of the present invention, a solution containing a transition metal can be prepared in a form in which the type and content of the doping element in a first solution containing a transition metal and a second solution containing a transition metal are different.

[0070] Specifically, as doping elements, for example, Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P and S can be used, and Zr is particularly preferred in order to improve the structural stability of lithium transition metal oxides.

[0071] When Zr is used as a dopant element, if the Zr content in the first solution containing a transition metal is greater than the Zr content in the second solution containing a transition metal, the average grain size of the core can be adjusted to be smaller than the average grain size of the shell.

[0072] Next, a solution containing transition metals is added to the reactor, and a co-precipitation reaction is carried out while adding an ammonium cation complexing agent and an alkaline aqueous solution, thereby preparing transition metal hydroxides in the form of secondary particles formed by primary particle agglomeration.

[0073] The ammonium cation complexing agent can be NH4OH, (NH4)2SO4, NH4NO3, NH4Cl, CH3COONH4, or (NH4)2CO3, and a mixture of at least one of them can be used. Furthermore, the ammonium cation complexing agent can be used in the form of an aqueous solution, and in this case, water, or a mixture of water and an organic solvent that is homogeneous with water (e.g., ethanol), can be used as the solvent.

[0074] The alkaline aqueous solution may contain at least one selected from NaOH, KOH, and Ca(OH)₂, and water, or a mixture of an organic solvent (e.g., ethanol) and water that is homogeneous with water, can be used as the solvent. In this case, the concentration of the alkaline aqueous solution can be in the range of 2M to 5M, for example, 3M to 4M. When the concentration of the alkaline aqueous solution meets the above range, precursor particles of uniform size can be formed, the formation time of the precursor particles is fast, and the yield is also excellent. The alkaline aqueous solution is added to adjust the pH of the reaction solution, wherein the amount of alkaline aqueous solution can be adjusted to maintain the pH at 9 to 12 during the coprecipitation reaction, and can be adjusted to preferably maintain the pH at 10.5 to 11.5.

[0075] According to the present invention, the temperature during the coprecipitation reaction can be in the range of 30°C to 60°C, for example, 30°C to 50°C. Because transition metal hydroxides are prepared within this temperature range, the coprecipitation reaction is easy to control and productivity can be improved. Outside this temperature range, such as below 30°C, the productivity decreases due to the loss of transition metal ions. Furthermore, above 60°C, the size of the primary particles is difficult to control due to excessive crystal growth, and the coprecipitation reaction is also difficult to control due to rapid ammonia evaporation.

[0076] The pH during the coprecipitation reaction can be in the range of 9 to 12, for example, 10.5 to 11.5. By conducting the coprecipitation reaction within this pH range, transition metal hydroxide particles with suitable particle size distribution and density can be prepared. Conversely, when the mixture is coprecipitated at a pH less than 9, there is a problem of decreased productivity due to the loss of transition metal ions, or when the mixture is coprecipitated at a pH greater than 12, there is a problem of secondary particle growth.

[0077] In one embodiment of the present invention, a first solution containing a transition metal is added to a reactor, and a co-precipitation reaction is carried out simultaneously with the addition of an alkaline aqueous solution and an ammonium cation complexing agent, thereby enabling the growth of a core in the form of secondary particles formed by primary particle agglomeration. When the average particle size D50 of the positive electrode active material precursor particles in the reaction solution reaches 85% or more, for example, 90% or more, of the total particle size, a second solution containing a transition metal is added to the reactor, and a co-precipitation reaction is carried out simultaneously with the addition of an alkaline aqueous solution and an ammonium cation complexing agent. By using the above method to grow a shell on the outside of the core, a positive electrode active material precursor can be prepared.

[0078] The positive electrode active material of the present invention can be prepared by mixing the above-mentioned positive electrode active material precursor with lithium-containing raw materials and sintering the mixture.

[0079] In this case, there are no particular restrictions on the lithium-containing raw materials, as long as they are compounds containing a lithium source. However, it is preferred that at least one selected from lithium carbonate (Li2CO3), lithium hydroxide (LiOH), LiNO3, CH3COOLi and Li2(COO)2 can be used.

[0080] Preferably, the positive electrode active material of the present invention can be prepared by mixing the above-mentioned positive electrode active material precursor and lithium-containing raw material at a molar ratio of 1.0 to 1.1, for example 1.03 to 1.1, and sintering at 600°C to 850°C for 3 to 30 hours.

[0081] When lithium-containing raw materials are mixed at a ratio lower than the above range, the capacity of the prepared positive electrode active material may decrease. Furthermore, when lithium-containing raw materials are mixed at a ratio higher than the above range, it is difficult to prepare the positive electrode active material because the particles sinter during the sintering process, the capacity may decrease, and separation of the positive electrode active material particles may occur after sintering.

[0082] Furthermore, at sintering temperatures below 600°C, the high-temperature stability of the battery may decrease because raw materials may remain in the particles due to incomplete reaction, and the structural stability may also decrease due to reduced bulk density and crystallinity. At sintering temperatures above 850°C, non-uniform particle growth may occur, and the volumetric capacity of the battery may decrease because the particle size increases excessively, thereby reducing the number of particles per unit area. Considering the particle size control, capacity, and stability of the obtained positive electrode active material particles, as well as the reduction of lithium-containing byproducts, the sintering temperature can be more preferably in the range of 700°C to 750°C.

[0083] Furthermore, when the sintering time is less than 3 hours, it is difficult to obtain a high degree of crystallinity positive electrode active material because the reaction time is too short. Moreover, when the sintering time is more than 30 hours, the particle size may increase excessively and the production efficiency may decrease.

[0084] In one embodiment of the present invention, since the amount of dopant in the shell is increased compared to the core by adding dopant in the sintering step, the average grain size of the core can be adjusted to be smaller than the average grain size of the shell.

[0085] Specifically, as doping elements, for example, Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P and S can be used, and Zr is particularly preferred in order to improve the structural stability of lithium transition metal oxides.

[0086] Based on the total number of moles of metal elements other than lithium contained in the entire core and shell, the content of the dopant element can be independently from 0.1 mol% to 2 mol%, for example, from 0.2 mol% to 1 mol%. For example, if the content of the dopant element in the core and shell is independently less than 0.1 mol%, the effect of the addition of the dopant element on improving structural stability and output characteristics may not be significant, and if the content of the dopant element is more than 2 mol%, the capacity may decrease and lithium byproducts may increase.

[0087] positive electrode

[0088] The positive electrode of the present invention comprises the above-described positive electrode active material of the present invention. Specifically, the positive electrode comprises a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material of the present invention. Since the positive electrode active material has been described above, its detailed description will be omitted, and only the remaining structure will be described in detail below.

[0089] The positive electrode current collector can contain a highly conductive metal, and there are no particular limitations as long as it is not reactive within the battery voltage range and the positive electrode active material layer can easily adhere to it. Examples of materials that can be used as the positive electrode current collector include stainless steel, aluminum, nickel, titanium, sintered carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. Furthermore, the thickness of the positive electrode current collector is typically from 3 μm to 500 μm, and microscopic irregularities can be formed on the surface of the current collector to improve adhesion to the positive electrode active material. The positive electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.

[0090] If necessary, the positive electrode active material layer may optionally include a conductive agent and a binder in addition to the positive electrode active material.

[0091] In this case, based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be from 80% to 99% by weight, for example, from 85% to 98.5% by weight. If the content of the positive electrode active material is within the above range, excellent capacity characteristics can be obtained.

[0092] Conductive agents are used to provide conductivity to the electrodes. Any conductive agent can be used without particular limitation, as long as it has suitable electronic conductivity without causing adverse chemical changes in the battery. Specific examples of conductive agents can be graphite (such as natural or artificial graphite), carbon-based materials (such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black, and carbon fibers), metal powders or fibers (such as copper, nickel, aluminum, and silver), conductive tubes (such as carbon nanotubes), conductive whiskers (such as zinc oxide whiskers and potassium titanate whiskers), conductive metal oxides (such as titanium oxide), or conductive polymers (such as polyphenylene derivatives), and any one or a mixture of two or more of these can be used. Based on the total weight of the positive electrode active material layer, the content of the conductive agent can be from 0.1% by weight to 15% by weight.

[0093] The adhesive improves the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. Specific examples of the adhesive can be polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, polymethyl methacrylate, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid and polymers whose hydrogen is replaced by lithium (Li), sodium (Na) or calcium (Ca), or various copolymers thereof, and any one or a mixture of two or more of them can be used. Based on the total weight of the positive electrode active material layer, the adhesive content can be from 0.1% by weight to 15% by weight.

[0094] The positive electrode can be prepared according to typical methods for preparing a positive electrode, the difference being the use of the aforementioned positive electrode active material. Specifically, the composition for forming the positive electrode active material layer is prepared by dissolving or dispersing the positive electrode active material and optionally a binder and a conductive agent in a solvent, coating the composition onto a positive electrode current collector, and preparing the positive electrode by drying and rolling the coated positive electrode current collector.

[0095] The solvent can be any solvent commonly used in this art and may include dimethyl sulfoxide (DMSO), isopropanol, N-methylpyrrolidone (NMP), dimethylformamide (DMF), acetone, or water, as well as any one or a mixture of two or more of these. The amount of solvent used is sufficient if it can dissolve or disperse the positive electrode active material, conductive agent, binder, and dispersant, and has a viscosity that provides excellent thickness uniformity during subsequent coating processes for preparing the positive electrode, taking into account the coating thickness and production yield.

[0096] Alternatively, as another method, the positive electrode can be prepared by casting a composition for forming the positive electrode active material layer onto a separate support, and then laminating a membrane separated from the support onto the positive electrode current collector.

[0097] Electrochemical equipment

[0098] Next, the electrochemical device of the present invention will be described. The electrochemical device of the present invention includes the above-described positive electrode of the present invention, wherein the electrochemical device may specifically be a battery or a capacitor, and, for example, a lithium secondary battery.

[0099] A lithium secondary battery specifically includes a positive electrode, a negative electrode facing the positive electrode, a separator disposed between the positive and negative electrodes, and an electrolyte. Since the positive electrode is the same as described above, its detailed description will be omitted, and only the remaining structures will be described in detail below.

[0100] In addition, the lithium secondary battery may optionally include a battery container that houses an electrode assembly containing a positive electrode, a negative electrode, and a separator, as well as a sealing component for sealing the battery container.

[0101] In a lithium secondary battery, the negative electrode includes a negative electrode current collector and a layer of negative electrode active material disposed on the negative electrode current collector.

[0102] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity without causing adverse chemical changes in the battery. Materials used include, for example, copper, stainless steel, aluminum, nickel, titanium, sintered carbon, or copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., as well as aluminum-cadmium alloys. Furthermore, the thickness of the negative electrode current collector can typically range from 3 μm to 500 μm, and, similar to the positive electrode current collector, microscopic irregularities can be formed on the surface of the current collector to improve the adhesion of the negative electrode active material. The negative electrode current collector can be used in various shapes, such as films, sheets, foils, meshes, porous bodies, foams, or nonwoven fabrics.

[0103] The negative electrode active material layer may optionally include a binder and a conductive agent in addition to the negative electrode active material.

[0104] As negative electrode active materials, compounds capable of reversibly inserting and de-intercalating lithium can be used. Specific examples of negative electrode active materials can be carbonaceous materials (such as artificial graphite, natural graphite, graphitized carbon fibers, and amorphous carbon), metallic materials that can be alloyed with lithium (such as silicon (Si), aluminum (Al), tin (Sn), lead (Pb), zinc (Zn), bismuth (Bi), indium (In), magnesium (Mg), gallium (Ga), cadmium (Cd), Si alloys, Sn alloys, or Al alloys), and metal oxides that can be doped and de-doped with lithium (such as SiO₂). β (0<β<2), SnO2, vanadium oxide, and lithium oxide) or composites comprising metallic and carbonaceous materials (such as Si-C composites or Sn-C composites), and mixtures of any one or more thereof may be used. Additionally, lithium metal films can be used as anode active materials. Furthermore, both low-crystallinity and high-crystallinity carbon can be used as carbon materials. Typical examples of low-crystallinity carbon can be soft carbon and hard carbon, while typical examples of high-crystallinity carbon can be irregular, planar, sheet-like, spherical, or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch-based carbon fibers, mesophase carbon microspheres, mesophase pitch, and high-temperature sintered carbon (such as petroleum or coal tar pitch-derived coke).

[0105] Based on the total weight of the negative electrode active material layer, the content of the negative electrode active material can be from 80% to 99% by weight.

[0106] The binder is a component that facilitates the bonding between the conductive agent, the active material, and the current collector, wherein the amount of binder added is typically from 0.1% to 10% by weight, based on the total weight of the negative electrode active material layer. Examples of binders may be polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), nitrile rubber, fluororubber, or various copolymers thereof.

[0107] A conductive agent is a component used to further improve the conductivity of the negative electrode active material. The amount of conductive agent added is less than 10% by weight, for example, less than 5% by weight, based on the total weight of the negative electrode active material layer. There are no particular limitations on the conductive agent, as long as it is conductive and does not cause adverse chemical changes in the battery. For example, conductive materials such as graphite (e.g., natural or artificial graphite), carbon black (e.g., acetylene black, Ketjen black, channel black, furnace black, lamp black, or thermally cracked carbon black), conductive fibers (e.g., carbon fibers or metal fibers), metal powders (e.g., fluorocarbon powders, aluminum powder, and nickel powder), conductive whiskers (e.g., zinc oxide whiskers and potassium titanate whiskers), conductive metal oxides (e.g., titanium oxide), or conductive polymers (e.g., polyphenylene derivatives) can be used.

[0108] The negative electrode active material layer can be prepared as follows: the composition for forming the negative electrode active material is prepared by dissolving or dispersing the negative electrode active material and optionally a binder and a conductive agent in a solvent, by coating it onto a negative electrode current collector and drying the coated negative electrode current collector, or by casting the composition for forming the negative electrode active material layer onto a separate support and then laminating a thin film separated from the support onto the negative electrode current collector.

[0109] In lithium-ion secondary batteries, the separator separates the negative electrode from the positive electrode and provides a migration path for lithium ions. Any separator can be used without particular limitation, as long as it is typically used in lithium-ion secondary batteries. Specifically, separators with high electrolyte retention capacity and low resistance to electrolyte ion transfer can be used. Porous polymer membranes can be used, such as those made of polyolefin polymers (e.g., ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers, or ethylene / methacrylate copolymers), or laminates having two or more layers. Alternatively, typical porous nonwoven fabrics can be used, such as those made of high-melting-point glass fibers or polyethylene terephthalate fibers. Furthermore, coated separators containing ceramic components or polymer materials can be used to ensure heat resistance or mechanical strength, and separators with single-layer or multi-layer structures can be optionally used.

[0110] In addition, the electrolyte used in this invention may include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes or molten inorganic electrolytes used in the preparation of lithium secondary batteries, but this invention is not limited thereto.

[0111] Specifically, electrolytes can contain organic solvents and lithium salts.

[0112] As organic solvents, any organic solvent can be used without particular limitation, as long as it can serve as a medium for the migration of ions participating in the electrochemical reactions of the battery. Specifically, as organic solvents, ester solvents (methyl acetate, ethyl acetate, γ-butyrolactone and ε-lactamolactone), ether solvents (such as dibutyl ether or tetrahydrofuran), ketone solvents (such as cyclohexanone), aromatic hydrocarbon solvents (such as benzene and fluorobenzene), or carbonate solvents (such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC)), alcohol solvents (such as ethanol and isopropanol), nitriles (such as R-CN, where R is a straight-chain, branched or cyclic C2-C20 hydrocarbon group, which may include double-bonded aromatic rings or ether bonds), amides (such as dimethylformamide), dioxolane (such as 1,3-dioxolane), or sulfolane can be used. Among these solvents, carbonate solvents can be used, and, for example, a mixture of cyclic carbonates (e.g., ethylene carbonate or propylene carbonate) with high ionic conductivity and high dielectric constant and low viscosity linear carbonate compounds (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) that can improve the charging / discharging performance of the battery can be used.

[0113] Lithium salts can be used without particular restrictions, as long as they are compounds that can provide lithium ions when used in lithium secondary batteries. Specifically, the anion of the lithium salt can be selected from F... - Cl - ,Br - I - NO3 - N(CN)2 - BF4 - CF3CF2SO3 - (CF3SO2)2N - (FSO2)2N - CF3CF2(CF3)2CO - (CF3SO2)2CH - (SF5)3C - (CF3SO2)3C - CF3(CF2)7SO3 - CF3CO2 - CH3CO2 - SCN - and (CF3CF2SO2)2N -At least one of the following can be used as a lithium salt: LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The lithium salt can be used in a concentration range from 0.1 M to 2.0 M. If the concentration of the lithium salt is within this range, excellent electrolyte performance can be obtained because the electrolyte can have suitable conductivity and viscosity, and lithium ions can migrate efficiently.

[0114] To improve battery life characteristics, suppress battery capacity degradation, and improve battery discharge capacity, in addition to the electrolyte components, at least one additive may be further included in the electrolyte, such as haloalkylene carbonate compounds (e.g., ethylene difluorocarbonate), pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-ethylene glycol dimethyl ether, triammonium hexaphosphate, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted oxazolidinones, N,N-substituted imidazolides, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride. In this case, the additive content can be from 0.1% by weight to 5% by weight, based on the total weight of the electrolyte.

[0115] As described above, lithium secondary batteries containing the positive electrode active material of the present invention stably exhibit excellent discharge capacity, output characteristics and lifespan characteristics, making them suitable for portable devices (such as mobile phones, laptops and digital cameras) and electric vehicles (such as hybrid electric vehicles (HEVs)).

[0116] Therefore, according to another embodiment of the present invention, a battery module comprising the above-mentioned lithium secondary battery as a unit cell and a battery pack comprising the battery module are provided.

[0117] Battery modules or battery packs can be used as power sources for at least one of the following medium to large-sized devices: power tools, electric vehicles (including electric vehicles (EVs), hybrid electric vehicles, and plug-in hybrid electric vehicles (PHEVs)), or energy storage systems.

[0118] There are no particular restrictions on the shape of lithium secondary batteries, but they can be cylindrical, prismatic, bag-shaped, or coin-shaped.

[0119] Lithium-ion batteries can be used not only as battery cells for powering small devices, but also as unit cells in medium and large battery modules containing multiple battery cells.

[0120] Examples of medium to large-sized equipment can be electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and energy storage systems, but medium to large-sized equipment is not limited to these.

[0121] Example 1

[0122] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 83:5:10:2, in order to prepare a 2M aqueous solution of the first transition metal.

[0123] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0124] Subsequently, after adding deionized water to the reactor, which was set to 45°C, the reactor was purged with nitrogen to remove dissolved oxygen, thereby generating a non-oxidizing atmosphere in the reactor. Then, 4M NaOH was added to maintain the pH in the reactor at 11.

[0125] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0126] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0127] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0128] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0129] Example 2

[0130] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, in order to prepare a 2M aqueous solution of the first transition metal.

[0131] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0132] Subsequently, after adding deionized water to the reactor, which was set to 45°C, the reactor was purged with nitrogen to remove dissolved oxygen, thereby generating a non-oxidizing atmosphere in the reactor. Then, 4M NaOH was added to maintain the pH in the reactor at 11.

[0133] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0134] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0135] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0136] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0137] Example 3

[0138] NiSO4, CoSO4, MnSO4, Al2(SO4)3 and Zr(SO4)2 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum:zirconium was 85:6.5:6.5:1.5:0.5 to prepare a 2M aqueous solution of the first transition metal.

[0139] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0140] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0141] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0142] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0143] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0144] LiOH was mixed with the obtained positive electrode active material precursor to make the ratio of Li:(Ni+Co+Mn+Al+Zr) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0145] Example 4

[0146] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, in order to prepare a 2M aqueous solution of the first transition metal.

[0147] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0148] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0149] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0150] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0151] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0152] LiOH, the obtained positive electrode active material precursor, and ZrO2 were mixed to make Li:(Ni+Co+Mn+Al):Zr 1.05:1:0.005, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0153] Example 5

[0154] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, in order to prepare a 2M aqueous solution of the first transition metal.

[0155] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a 1.5 M aqueous solution of the second transition metal.

[0156] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0157] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0158] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0159] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0160] LiOH, the obtained positive electrode active material precursor, and ZrO2 were mixed to make Li:(Ni+Co+Mn+Al):Zr 1.05:1:0.005, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0161] Example 6

[0162] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, to prepare a 2.5 M aqueous solution of the first transition metal.

[0163] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0164] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0165] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0166] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0167] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0168] LiOH, the obtained positive electrode active material precursor, and ZrO2 were mixed to make Li:(Ni+Co+Mn+Al):Zr 1.05:1:0.005, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0169] Comparative Example 1

[0170] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, to prepare a 2M aqueous solution of transition metals.

[0171] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0172] Subsequently, aqueous solutions of transition metals, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form precursor particles.

[0173] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0174] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0175] Comparative Example 2

[0176] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, in order to prepare a 2M aqueous solution of transition metals.

[0177] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0178] Subsequently, aqueous solutions of transition metals, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form precursor particles.

[0179] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0180] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0181] Comparative Example 3

[0182] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum was 83:5:10:2, in order to prepare a 2M aqueous solution of transition metals.

[0183] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0184] Subsequently, aqueous solutions of transition metals, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form precursor particles.

[0185] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0186] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0187] Comparative Example 4

[0188] NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in amounts such that the molar ratio of nickel:cobalt:manganese:aluminum was 90:4:4:2, to prepare a 2M aqueous solution of the first transition metal.

[0189] In addition, NiSO4, CoSO4, MnSO4 and Al2(SO4)3 were mixed in distilled water in such amounts that the molar ratio of nickel:cobalt:manganese:aluminum was 85:6.5:6.5:2, in order to prepare a second transition metal aqueous solution with a concentration of 2M.

[0190] Subsequently, deionized water was added to the reactor, which was set to 45°C. The reactor was then purged with nitrogen to remove dissolved oxygen, thereby creating a non-oxidizing atmosphere in the reactor. Afterward, 4M NaOH was added to maintain the pH in the reactor at 11.

[0191] Subsequently, aqueous solutions of the first transition metal, sodium hydroxide, and ammonia were added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, with the reaction temperature set at 45°C and pH at 11, and a co-precipitation reaction was carried out for 15 hours to form the nucleus of the precursor particles.

[0192] Then, when the average particle size D50 of the precursor particles in the reaction solution reaches 14 μm, the second transition metal aqueous solution, sodium hydroxide aqueous solution, and ammonia aqueous solution are added to the reactor at rates of 4 mL / min, 4 mL / min, and 1 mL / min, respectively, to set the reaction temperature at 45 °C and the pH at 11, and an additional co-precipitation reaction is carried out for 1 hour to grow the shell of the precursor particles.

[0193] When the average particle size D50 of the precursor particles reaches 15 μm, the reaction is terminated, and the precursor particles are separated from the reaction solution by filtration and dried to obtain the positive electrode active material precursor.

[0194] LiOH was mixed with the obtained positive electrode active material precursor to make Li:(Ni+Co+Mn+Al) 1.05:1, and sintered at 730℃ for 15 hours to prepare lithium transition metal oxide with an average particle size D50 of 15 μm.

[0195] Experimental Example 1

[0196] The average grain size of the core and shell of the lithium transition metal oxide particles prepared in Examples 1 to 6 and Comparative Examples 1 to 4 was measured using a TITAN G2 HR-TEM as described below. The measurement results are shown in Table 1.

[0197] [Table 1]

[0198] Example 1 120 200 Example 2 160 200 Example 3 120 200 Example 4 120 180 Example 5 120 260 Example 6 80 200 Comparative Example 1 200 200 Comparative Example 2 160 160 Comparative Example 3 120 120 Comparative Example 4 200 160

[0199] Experimental Example 2: Determination of Initial Discharge Capacity

[0200] The various lithium transition metal oxides prepared in the Examples and Comparative Examples as positive electrode active materials, carbon black as a conductive agent, and polyvinylidene fluoride as a binder were mixed in N-methylpyrrolidone solvent such that the weight ratio of positive electrode active material: conductive agent: binder was 96:2:2, thereby preparing a positive electrode slurry. The positive electrode slurry was coated on one surface of an aluminum current collector, dried at 130°C, and subsequently rolled to prepare the positive electrode.

[0201] Next, the negative electrode active material (natural graphite), conductive agent (carbon black), and binder (polyvinylidene fluoride, PVDF) are mixed in N-methylpyrrolidone solvent at a weight ratio of 95:2:3 to prepare the negative electrode slurry. The negative electrode slurry is then coated onto a copper current collector, dried, and rolled to prepare the negative electrode.

[0202] After fabricating an electrode assembly by placing a porous polyethylene separator between the positive and negative electrodes obtained above, the electrode assembly is placed into a battery casing, and an electrolyte solution is injected into the casing to prepare individual lithium secondary batteries. In this case, as the electrolyte solution, an electrolyte solution obtained by dissolving 2% by weight of vinylene carbonate (VC) and 1M LiPF6 in an organic solvent (ethylene carbonate (EC), dimethyl carbonate (DMC), and ethyl methyl carbonate (EMC) mixed in a 3:4:3 ratio) is injected to prepare the lithium secondary battery.

[0203] Each lithium secondary battery prepared as described above was charged to 4.25V at a constant current of 0.1C at 25°C, and then discharged to 2.5V at a constant current of 0.1C to measure the initial discharge capacity.

[0204] [Table 2]

[0205] Example 1 206 Example 2 208 Example 3 206 Example 4 206 Example 5 205 Example 6 203 Comparative Example 1 209 Comparative Example 2 207 Comparative Example 3 203 Comparative Example 4 208

[0206] As shown in Table 2, it can be confirmed that the secondary batteries containing lithium transition metal oxide particles prepared in Examples 1 to 6 and Comparative Examples 1 to 4 have similar initial discharge capacities.

[0207] Experimental Example 3: Lifetime Characteristics Evaluation

[0208] Each lithium secondary battery prepared in Experimental Example 2 was charged to 4.25V at a constant current of 0.3C at 25°C and discharged to 2.5V at a constant current of 0.3C, which was defined as one cycle. After 100 charge-discharge cycles, the capacity retention rate after 100 cycles was measured.

[0209] [Table 3]

[0210] Example 1 96 Example 2 95 Example 3 96 Example 4 96 Example 5 95 Example 6 96 Comparative Example 1 75 Comparative Example 2 90 Comparative Example 3 93 Comparative Example 4 91

[0211] As shown in Table 3, since the secondary battery containing the lithium transition metal particles prepared in Examples 1 to 6 had a higher capacity retention rate after 100 cycles compared to the secondary battery containing the lithium transition metal particles prepared in Comparative Examples 1 to 4, it can be confirmed that the secondary battery containing the lithium transition metal particles prepared in Examples 1 to 6 has excellent cycle characteristics.

Claims

1. A positive electrode active material for lithium secondary batteries, the positive electrode active material comprising lithium transition metal oxide particles, the lithium transition metal oxide particles having a core-shell structure including a core portion and a shell portion disposed on the surface of the core portion, in, the average grain size of the core portion is smaller than the average grain size of the shell portion, and the content of nickel in all transition metals contained in the core portion and the shell portion is 80 atm% or more, wherein the difference between the average grain size of the core portion and the average grain size of the shell portion is 20 nm to 150 nm, wherein, in the lithium transition metal oxide, the mole fraction of nickel in all transition metals of the core portion is smaller than the mole fraction of nickel in all transition metals of the shell portion.

2. The positive electrode active material for lithium secondary batteries as described in claim 1, wherein, The difference between the average grain size of the core portion and the average grain size of the shell portion is 30 nm to 100 nm.

3. The positive electrode active material for lithium secondary batteries as described in claim 1, wherein, The average grain size of the core portion is 100 nm to 180 nm.

4. The positive electrode active material for lithium secondary batteries as described in claim 1, wherein, The average grain size of the shell portion is 180 nm to 250 nm.

5. The positive electrode active material for lithium secondary batteries as described in claim 1, wherein, The core portion has a composition represented by Chemical Formula 1: [Chemical Formula 1] Li x1 Ni a1 Co b1 Mr c1 Al d1 M 1 e1 O2 In chemical formula 1, M 1 It is selected from at least one of the following groups: zirconium (Zr), boron (B), tungsten (W), magnesium (Mg), cerium (Ce), hafnium (Hf), tantalum (Ta), lanthanum (La), titanium (Ti), strontium (Sr), barium (Ba), fluorine (F), phosphorus (P), and sulfur (S). 0.90≤x1≤1.1, 0.80≤a1≤0.95, 0<b1<0.20, 0<c1<0.20, 0<d1≤0.10 and 0≤e1<0.

10.

6. The positive electrode active material for lithium secondary batteries as described in claim 1, wherein, The shell portion has a composition represented by Chemical Formula 2: [Chemical Formula 2] Li x2 Ni a2 Co b2 Mr c2 Al d2 M 2 e2 O2 In chemical formula 2, M 2 It is selected from at least one of the group consisting of Zr, B, W, Mg, Ce, Hf, Ta, La, Ti, Sr, Ba, F, P, and S, and 0.90≤x2≤1.1, 0.83≤a2<1.0, 0<b2<0.17, 0<c2<0.17, 0<d2≤0.10 and 0≤e2<0.

10.

7. A positive electrode, comprising the positive electrode active material according to any one of claims 1 to 6.

8. A lithium secondary battery, comprising the positive electrode according to claim 7, a negative electrode, a separator disposed between the positive electrode and the negative electrode, and an electrolyte.

Citation Information

Patent Citations

  • Methods and systems for lowering blood pressure through reduction of ventricle filling

    KR1020210024668A

  • Nickel-based active material precursor for lithium secondary battery, method of preparing the same, nickel-based active material for lithium secondary battery formed therefrom, and lithium secondary battery including positive electrode including nickel-based active material

    US20200119351A1

  • KR20210006252A